Transport theories applied to the study of convoy electron production - Martiarena, Maria Luz; Garibotti, Carlos R. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Martiarena, Maria Luz Comisión Nacional de Energía Atómica; Argentina